PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Yufi Latmini Lasari; Amelia Putri; Zola Akista Utami (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This research is motivated by the implementation of a scientific approach in thematic learning that has not been implemented fully and optimally so that the learning process that is carried out makes students easily bored and less attentive to learning. This study aims to describe how the planning, implementation, and evaluation of the application of a scientific approach in thematic learning in Theme 7 Sub-theme 3 Learning 1-6 in grade IV SD Negeri 13 Padang Panjang Timur. This type of research is descriptive qualitative research with a case study approach. The subjects of this study were fourth-grade teachers, fourth-grade students, and school principals. Methods of data collection using observation, interviews, and documentation studies. The results of this study indicate that planning activities are carried out by the teacher through several stages by compiling a syllabus, compiling lesson plans, and preparing thematic books and other learning resources. Implementation activities are carried out by teachers and students through five steps of a scientific approach, namely observing, asking questions, gathering information, associating, and communicating. Evaluation activities are carried out by teachers through authentic assessments to assess aspects of students' attitudes, knowledge, and skills.